González Porta, Mario Ariel, Estudos Neokantianos, Ed. Loyola, San Pablo, 2011, 322 pp. - Lucchessi, Laura Pelegrín (Universidad Pedagógica y Tecnológica de Colombia, 2016)
González Porta, Mario Ariel, Estudos Neokantianos, Ed. Loyola, San Pablo, 2011, 322 pp.